Nilai-Nilai Lokal dalam Al-Qur'an dan Terjemahan Manuskripnya dalam Bahasa Madura - Jati, Wasisto Raharjo; Kirwan; Misbahul Wani (Jurnal Lektur Keagamaan, 2025)
This study examines the emergence and development of Qur’an translation into Madurese, focusing on the work of lecturers at IAIN Madura under the directive of the Ministry of Religious Affairs of the Republic of Indonesia. Employing Nashruddin Baidan’s translation theory, particularly his framework of interpretive periodization in Arabic, this research adapts this approach to the context of Qur’anic translation into a regional language. Using qualitative descriptive analysis, the study traces the historical trajectory of Madurese Qur’an translation, beginning with the initiatives of Jema’ah Pengajian Surabaya (JPS), followed by the Institute for Translation and Study of the Qur’an (LP2Q), and culminating in the contributions of IAIN Madura. Findings suggest that the IAIN Madura project represents a developmental phase in the ongoing process of Qur’an translation into Madurese. The translation adopts a tafsīriyyah model characterized by dynamic adaptation of target-language grammar. A distinctive feature is the integration of the Madurese language hierarchy (bhâsa èngghi bhunten, bhâsa tèngghi/alos, bhâsa èngghi enten, and bhâsa ènjhâ’ iyâ), reflecting local cultural values. The Pamekasan–Sumenep dialect serves as the linguistic basis. The translation is guided by three principles: grounding Qur’anic values, advancing religious moderation and preserving regional linguistic heritage. Key references include Tafsīr Jalālain, Tafsīr Ibn Kathīr, and official translations published by the Ministry of Religious Affairs.